Sex, Race, and Motel Guests: Another Look at King v Barclay - HAMILL, SARAH (My University, 2017)
The 1961 case of King v Barclay is something of a footnote in the history of discrimination against Black Canadians. If it is cited at all, it is usually cited alongside the more famous racism cases, such as Christie v York, as proof of the widespread nature of racism in Canada. In this paper, I re-read the trial decision and examine the original case file to show that the facts of King and the racism in the case are more complex than usually realized. King emerged out of a series of errors from both King and Barclay’s Motel which resulted in the latter assuming, or seeming to assume, that King wished to visit two prostitutes working out of the motel. For obvious reasons, however, Barclay’s Motel could not state such an allegation explicitly as that would have been tantamount to admitting that they knew the women in question were prostitutes. In order to recapture the full legal and social contexts of King this paper examines both the history of racial discrimination in public accommodations and the longstanding struggle to prevent prostitutes from using such accommodations to ply their trade. The paper also argues that King’s legal action, even though he lost in court, was ultimately successful in that it prompted a legislative amendment, which removed the technicality upon which King turned.
PUBLISHED
Keywords: Canadian law; Racism; Discrimination; CANADA; Canada; Canadian History; Legal History; discrimination and marginalization; legal history